An Interdisciplinary Perspective on Greenland’s Changing Coastal Margins - Fiammetta Straneo; Donald Slater; Caroline Bouchard; Mattias Cape; Mark Carey; Lorenzo Ciannelli; James Holte; Patricia Matrai; Kristin Laidre; Christopher Little; Lorenz Meire; Helene Seroussi; et al. (Oceanography, 2022)
Greenland’s coastal margins are influenced by the confluence of Arctic and Atlantic waters, sea ice, icebergs, and meltwater from the ice sheet. Hundreds of spectacular glacial fjords cut through the coastline and support thriving marine ecosystems and, in some places, adjacent Greenlandic communities. Rising air and ocean temperatures, as well as glacier and sea-ice retreat, are impacting the conditions that support these systems. Projecting how these regions and their communities will evolve requires understanding both the large-scale climate variability and the regional-scale web of physical, biological, and social interactions. Here, we describe pan-Greenland physical, biological, and social settings and show how they are shaped by the ocean, the atmosphere, and the ice sheet. Next, we focus on two communities, Qaanaaq in Northwest Greenland, exposed to Arctic variability, and Ammassalik in Southeast Greenland, exposed to Atlantic variability. We show that while their climates today are similar to those of the warm 1930s–1940s, temperatures are projected to soon exceed those of the last 100 years at both locations. Existing biological records, including fisheries, provide some insight on ecosystem variability, but they are too short to discern robust patterns. To determine how these systems will evolve in the future requires an improved understanding of the linkages and external factors shaping the ecosystem and community response. This interdisciplinary study exemplifies a first step in a systems approach to investigating the evolution of Greenland’s coastal margins.

The Case for a Sustained Greenland Ice Sheet-Ocean Observing System (GrIOOS) - Fiammetta Straneo; David A. Sutherland; Leigh Stearns; Ginny Catania; Patrick Heimbach; Twila Moon; Mattias R. Cape; Kristin L. Laidre; Dave Barber; Søren Rysgaard; Ruth Mottram; Steffen Olsen; et al. (Frontiers in Marine Science, 2019)